Identity Issues: Turkish-Tatar Community in Dobrogea - Alexe, Cristina Mihaela (European Journal of Multidisciplinary Studies, 2023)
Recognized as the area with the richest ethnic mosaic in Romania, Dobrogea can be a model of interculturality for the other geographical areas of the country, as there is a model of relationship that could be replicated in other regions where there is interethnic coexistence. As far as the communities in the south-eastern part of Romania are concerned, it should be noted that, over time, it has been noticed how most people associate the term "Dobrogea" with the label "seaside".  It could be said that the overwhelming majority of tourists are more attracted by this idea (possibly 'delta'), 'beach', 'fun' than by getting to know the region, the local people, the history of this place, visiting cultural-historical sites. This is why Dobrogea remains for many Romanians "an unknown in their own home".
Keywords: identity, ethnic mosaic, Romania, interculturality, culture, solidarity, social identity